2013
DOI: 10.1002/chem.201302354
|View full text |Cite
|
Sign up to set email alerts
|

Application of H/D Exchange to Hydrogen Bonding in Small Molecules

Abstract: Do you recognize me? A series of simple amides has been used to demonstrate the application of hydrogen/deuterium exchange in small‐molecule hydrogen bonding. By comparison with similar controls, the degree of protection from H/D exchange can provide insight into the degree of hydrogen bonding (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Very recently, during the preparation of this manuscript, the synthesis of 5, alongside with the spectral data (though without 1 H and 13 C NMR assignment), has been published. To confirm this tentative identification we synthesized the mentioned compound starting from benzoyl chloride and methyl anthranilate in the presence of Et 3 N following the procedure of Schneider et al 27 and the structure of the synthetized compound was confirmed by 1D and 2D NMR (Fig. 31 of its mass spectra with those from MS libraries suggested that it contained an anthranilate moiety and that it could be an amide of benzoic acid.…”
Section: Resultsmentioning
confidence: 94%
“…Very recently, during the preparation of this manuscript, the synthesis of 5, alongside with the spectral data (though without 1 H and 13 C NMR assignment), has been published. To confirm this tentative identification we synthesized the mentioned compound starting from benzoyl chloride and methyl anthranilate in the presence of Et 3 N following the procedure of Schneider et al 27 and the structure of the synthetized compound was confirmed by 1D and 2D NMR (Fig. 31 of its mass spectra with those from MS libraries suggested that it contained an anthranilate moiety and that it could be an amide of benzoic acid.…”
Section: Resultsmentioning
confidence: 94%
“…The H/D exchange study is utilized to identify the hydrogen bond donors and the acceptors in the molecules using 1 H NMR spectroscopy 43 . Recently the effect of hydrogen bonding on H/D exchange rate in methoxy and keto substituted benzanilides 44 have been reported. It is well known that the rate of H/D exchange is not only dependent on the strength of the hydrogen bond, but also dependent on the electronic effect of the substituents.…”
Section: Introductionmentioning
confidence: 99%
“…Amine tetralone 5 in the presence of benzoyl chloride (BzCl), triethylamine (Et 3 N) and dichloromethane (DCM) as solvent gave benzoyl protected amine 7c in 89% yield (entry 1). 32 The tosyl protected amine tetralone 7d was obtained in 96% yield in pyridine with tosyl chloride (p-TsCl) (entry 2). 33 In a similar manner, base labile Fmoc protected amine 7e was formed in 98% yield with 9-fluorenylmethyloxycarbonyl chloride (Fmoc-Cl) and pyridine in DCM (entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, phenol 1g was also protected with benzoyl group in 94% yield using BzCl and Et 3 N as a base (entry 2). 32 Methyl ethers (1h and 1b) were first demethylated using sodium ethanethiolate (generated in situ) in dimethylformamide (DMF) at 140 o C giving the corresponding phenol, 39,40 which were acetylated under standard conditions (entries 3 and 4).…”
Section: Resultsmentioning
confidence: 99%